Abusive Supervision and Employee Creativity: The Mediating Effect of Role Identification and Organizational Support - Ke, Wenjing; Yu, Shun-Chi (International Journal of Multidisciplinary in Management and Tourism, 2023)
Enhancing employee creativity is one of the biggest challenges for organizations because business environments are fast-paced and extremely competitive. Employee creativity is the extent to which employees can solve problems through concrete and creative solutions, and generate novel business and operations ideas to improve productivity, competitiveness and business performance. The extant literature shows a big proportion of studies examining the effect of the positive aspects of leadership, such as transformational leadership, on employee creativity, and rarely relating to abusive leadership. This study, thus, aims to fill a gap. Building on the theory of organizational climate, this study proposes role identification and organizational support to mediate the relationship between abusive leadership and employee creativity. The aim of this study is twofold; to test the negative relationship between abusive leadership and employee creativity, and to examine the mediating roles of role identification and organizational support in the dynamics of interest. A self-administered survey tool was employed in this study for data collection, which draws the participation of three hundred and fifty-four corporate employees, both general employees and management staff of twelve companies involved in the information technology industry located in Beijing, Guangzhou, Chengdu, Nanjing, and Shenzhen. The study found that abusive supervision negatively influenced role identity and organizational support. Role identification partially mediated the relationship between abusive supervision and organizational support. While organizational support mediated the relationship between role identification and employee creativity, the negative effect of abusive supervision on employee creativity influenced role identification and organizational support. Creativity was found to have a mediating effect on role identification and organizational support through abusive supervision in the relational pathway. Thus, the study found inconsistent effects of abusive supervision on employee creativity, mediating role identification and organizational support, and explored role identity theory to inform the study of employee creativity.